GAMIFIKATSIYA VA BADGE/LEADERBOARD’LAR: SCIENCE MOTIVATSIYASINI KUCHAYTIRISH (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This thesis analyzes the issue of increasing student motivation through the use of gamification elements, in particular badges (digital badges) and leaderboards (rating tables), in teaching SCIENCE subjects. In the educational process, gamification technologies enhance students' desire for competitiveness, self-expression, achievement and success. Badges and leaderboards make student activity visible, strengthen incentive mechanisms, and increase motivation through internal and external factors. The study scientifically covers the didactic and psychological foundations of gamification elements, as well as their effectiveness in SCIENCE subjects.